Research on Dual Innovation Development Mechanism of Digitally Enabled Manufacturing Enterprises - Wang, Zhen; Yang, Shiyu; Xu, Xiangdong (International Journal of Scientific Research and Management (IJSRM), 2024)
Digitalization is the key driving force in today's world to promote innovation and optimize the development of high performance, digital integration as well as high-quality development has long been the center of gravity of the development of manufacturing enterprises. With the continuous development of digital technology, digital empowerment of manufacturing enterprises dual innovation and development is facing important challenges, mainly manifested in the technical application of the landing is not strong, the lack of policy uncertainty and support, the scarcity of digital composite talents, digital empowerment of the manufacturing industry feedback response delays and other aspects. Based on this, this paper describes the internal mechanism of digital empowerment and dual innovation development, from the digital empowerment of manufacturing enterprises dual innovation development mechanism implementation strategy and the development of the mechanism of the effect of the evaluation system in two aspects, to explain the digital empowerment of how to promote dual innovation by enhancing the ability of the enterprise; based on the innovation behavior of the enterprise, explore the digital empowerment of manufacturing enterprises under the development of dual innovation path for the development of a more practical and feasible program. Based on the innovation behavior of enterprises, we explore the development path of dual innovation in manufacturing enterprises under digital empowerment, and develop more practical programs for enterprises.